2020
DOI: 10.5194/aab-63-493-2020
|View full text |Cite
|
Sign up to set email alerts
|

Association of <i>β</i>-casein gene polymorphism with milk composition traits of Egyptian Maghrebi camels (<i>Camelus dromedarius</i>)

Abstract: Abstract. The objectives of this study were to detect the polymorphism of 2126A∕G SNP in the β-casein (CSN2) gene among Egyptian Maghrebi camels and to investigate the association of 2126A∕G SNP genotypes, parity, lactation stage, and temperature–humidity index (THI) with the milk composition traits of Maghrebi camels. Sixty-eight hair samples were collected from three different populations of Maghrebi camels for DNA extraction. Fat, protein, total solids, solids-not-fat, and lactose percentages were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…One ecotype, Ardhaoui Medenine, deviated from the aver-age CSN2 G allele frequency (0.550 vs. 0.462) of the total population, whereas in the Abidi camels, the 2 alleles (0.50) were perfectly balanced. Although the sample size was small and similar in both populations, this result was at odds with findings from studies of a similarly-sized population (Pauciullo et al, 2014;Nowier and Ramadan, 2020). The β-CN protein is both abundant and important to camel milk processing.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…One ecotype, Ardhaoui Medenine, deviated from the aver-age CSN2 G allele frequency (0.550 vs. 0.462) of the total population, whereas in the Abidi camels, the 2 alleles (0.50) were perfectly balanced. Although the sample size was small and similar in both populations, this result was at odds with findings from studies of a similarly-sized population (Pauciullo et al, 2014;Nowier and Ramadan, 2020). The β-CN protein is both abundant and important to camel milk processing.…”
Section: Discussioncontrasting
confidence: 57%
“…The β-CN protein is both abundant and important to camel milk processing. Nowier and Ramadan (2020) proposed an association study of β-CN and milk chemical composition traits in Maghrebi camel breeds because high levels of the protein and acidity in A/A-genotyped individuals suggest an affinity for cheese processing. Our data confirmed that allele A is more frequent in the Tunisian popula- Different superscripts mean significant differences (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such gene is the K-CN gene, which has been studied for its polymorphisms and their effects on milk traits and properties [12]. Another gene involved in MAS is the β-casein (CSN2) gene, which has a specific SNP (2126 A/G) that has been associated with milk composition traits in Maghrebi camels [13]. Additionally, the alphalactalbumin gene has been studied for its genetic polymorphisms and their relationship with milk protein concentration in Maghrebi camels.…”
Section: Marker Assisted Selectionmentioning
confidence: 99%
“…A genetic variation in kappa-casein may also indicate that the mature protein is associated with other polymorphisms in non-coding sequences (promoter). A mutation could cause some alleles to express differently, such as the two main alleles of bovine cattle's kappa-casein gene (30) .…”
Section: Observed Genotypesmentioning
confidence: 99%